Nanocomposites for extrinsic self-healing polymer Materials: A comprehensive review of their repair behaviour - Arunima Verma; Kumud Bhushan; Harwinder Singh (Results in Chemistry)
The ability of self-healing materials to detect damage and “autonomously” repair it has garnered significant attention in recent decades. This review explores the critical role of nanomaterials and nanostructures in enhancing the healing process, owing to their extensive surface area, abundant functional groups, and unique properties. From a historical perspective, it traces key developments in the design philosophy behind polymer self-healing and provides a comprehensive overview of recent advancements that leverage nanotechnology to improve healing efficiency and introduce novel functionalities. The literature is categorized into three main areas: (i) Material damage causes, typical repairs, and self-healing benefits, (ii) material properties essential for self-healing evaluation, (iii) characterization methods used to assess the healing capacity of these systems. Advanced techniques are discussed to elucidate micro- and nanoscale interactions at polymer interfaces, emphasizing their role in improving self-healing mechanisms. This review concludes by highlighting the practical implications of these advancements and outlining future directions for research, underscoring their potential to revolutionize the development of durable, multifunctional materials for real-world applications.